The rise of mutual funds an insider's view - Fink, Matthew P. (New York ; Oxford : Oxford University Press, 2008)
In 1940 few Americans had heard of mutual funds. Today, U.S. mutual funds are the largest financial industry in the world with over 88 million shareholders and over $11 trillion in assets. Matthew P. Fink describes the developments that have produced mutual funds' long history of success.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mutual funds -- History